2012
DOI: 10.1021/jp301366r
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Molecular Dynamics Study of the Dehydroxylation Reaction in a Smectite Model

Abstract: We have studied the dehydroxylation reaction in a smectite model, with the purpose of determining the influence of the octahedral layer composition and the possible role of the interlayer cations. Employing ab initio molecular dynamics and with the help of metadynamics for accelerating the reaction, we study the two possible mechanisms for the formation of the first water molecule. In the first mechanism, the migration of the proton across the octahedral vacancy takes place by means of a stable intermediate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
7
16
1
Order By: Relevance
“…In addition, we conclude that in the tetrahedral layer a bridged hydroxyl group in the arrangement Al···HO–Si does not exist, because an 27 Al coupled signal at about 4 ppm cannot be observed. The structure of smectites during RHX was studied using ab initio molecular models by Muñoz-Santiburcio et al Their calculations show no presence of bridging OH groups.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition, we conclude that in the tetrahedral layer a bridged hydroxyl group in the arrangement Al···HO–Si does not exist, because an 27 Al coupled signal at about 4 ppm cannot be observed. The structure of smectites during RHX was studied using ab initio molecular models by Muñoz-Santiburcio et al Their calculations show no presence of bridging OH groups.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Continuing with the same idea that phyllosilicates are clear evidence for aqueous alteration during the accretion of CCs, the literature contains a set of computational chemistry studies based on ab initio molecular dynamic simulations essentially focused on the dehydroxylation of two phyllosilicates: pyrophillite (Molina-Montes et al, 2008a;Molina-Montes et al, 2008b;Molina-Montes et al, 2010) and smectite (Muñoz-Santiburcio et al, 2012;Muñoz-Santiburcio et al, 2016). These authors identified different competitive paths for the dehydroxilation of these hydrous minerals, but the major conclusion is that in order to carry out the reaction high temperatures (1500 K) are required because of the high activation energies (about 60 kcal mol -1 for pyrophillite and 50 kcal mol -1 for smectite).…”
Section: Atomistic Pictures Of Material/water Interfaces Relevant For...mentioning
confidence: 99%
“…The system was equilibrated for more than 10 ps, during which we adjusted on-the-fly the value of γD. In order to observe the diffusion of the MEL from the interlayer space to the bulk water reservoir out of the mineral in a computationally affordable time, we exploit Metadynamics [74], which was used satisfactorily in these systems previously [75,76]. In this work, we used the Multiple-Walker implementation for a more efficient sampling of the free energy surface (FES) [77].…”
Section: Computational Detailsmentioning
confidence: 99%